Variable stiffness actuators: The user's point of view. (May 2015) - Grioli, Giorgio; Wolf, Sebastian; Garabini, Manolo; Catalano, Manuel; Burdet, Etienne; Caldwell, Darwin; Carloni, Raffaella; Friedl, Werner; Grebenstein, Markus; Laffranchi, Matteo; Lefeber, Dirk; Stramigioli, Stefano; et al.
Since their introduction in the early years of this century, variable stiffness actuators (VSA) witnessed a sustained growth of interest in the research community, as shown by the growing number of publications. While many consider VSA very interesting for applications, one of the factors hindering their further diffusion is the relatively new conceptual structure of this technology. When choosing a VSA for their application, educated practitioners, who are used to choosing robot actuators based on standardized procedures and uniformly presented data, would be confronted with an inhomogeneous and rather disorganized mass of information coming mostly from scientific publications. In this paper, the authors consider how the design procedures and data presentation of a generic VSA could be organized so as to minimize the engineer's effort in choosing the actuator type and size that would best fit the application needs. The reader is led through the list of the most important parameters that will determine the ultimate performance of their VSA robot, and influence both the mechanical design and the controller shape. This set of parameters extends the description of a traditional electric actuator with quantities describing the capability of the VSA to change its output stiffness. As an instrument for the end-user, the VSA datasheet is intended to be a compact, self-contained description of an actuator that summarizes all of the salient characteristics that the user must be aware of when choosing a device for their application. At the end some examples of compiled VSA datasheets are reported, as well as a few examples of actuator selection procedures.